2016
DOI: 10.1111/bcpt.12678
|View full text |Cite
|
Sign up to set email alerts
|

Students and Doctors are Unaware of the Cost of Drugs they Frequently Prescribe

Abstract: Given the increasing healthcare costs of an ageing population, there is growing interest in rational prescribing, which takes costs of medication into account. We aimed to gain insight into the attitude to and knowledge of medication costs of medical students and doctors in daily practice. This was a cross-sectional electronic survey among medical students (bachelor/master) and doctors (consultants/registrars). Attitude to costs was evaluated using a cost-consciousness scale. In open questions, the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…10,11 Schutte et al and Long et al are advocating medical schools should consider incorporating cost awareness as part of their curriculum in order to raise cost awareness in tomorrow’s doctors. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Schutte et al and Long et al are advocating medical schools should consider incorporating cost awareness as part of their curriculum in order to raise cost awareness in tomorrow’s doctors. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we found that the GPs are more likely to make changes in treatment to adhere to new recommendations if they perceive them to be based on factors that are important for a patient’s health rather than just related to cost [ 14 ]. Similarly, it has been reported that medical doctors and students are unaware of the costs of the medicines that they prescribe even though they state that being aware of the costs is important [ 27 ]. Many countries have introduced reforms to reduce costs of medicines [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible for our physicians to correctly estimate the burden of medication expenses on our patients as they highly undermine the cost of their prescribed drugs. The literature also identifies the existence of inconsistent estimation of drug cost by the physicians [ 20 ]. Although both our patients and physicians preferred rapid-acting drugs in the form of once-daily dosing and fixed-dose combinations, we could find no substantial studies with which to compare our results.…”
Section: Discussionmentioning
confidence: 99%